2016
DOI: 10.1039/c6dt00370b
|View full text |Cite
|
Sign up to set email alerts
|

Multinuclear silver(i) XPhos complexes with cyclooctatetraene: photochemical C–C bond cleavage of acetonitrile and cyanide bridged Ag cluster formation

Abstract: Cationic mono-, di-, tri- and tetra-nuclear silver complexes with Buchwald-type phosphane (XPhos) and cyclooctatetraene (COT) have been synthesized and characterized. Formation of [(XPhos-Ag)n(COT)][SbF6]n (n = 1 and 2) complexes was confirmed by single-crystal X-ray crystallography and multinuclear NMR spectroscopy. Variable-temperature NMR spectroscopy in CD2Cl2 solution shows the fluxionality of the COT ring in the mono-Ag(i) XPhos complex. Fluxionality of COT was also confirmed in the case of the di-Ag(i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For a long time, the triphenylphosphine–gold π-complexes were considered unstable in solution. , However, we have recently shown that these complexes are much more stable than what was previously published and we were also able to characterize them by X-ray for the first time . Other silver­(I) and gold­(I) π-complexes utilizing phosphines and other ligands were characterized previously as well. …”
Section: Introductionmentioning
confidence: 71%
“…For a long time, the triphenylphosphine–gold π-complexes were considered unstable in solution. , However, we have recently shown that these complexes are much more stable than what was previously published and we were also able to characterize them by X-ray for the first time . Other silver­(I) and gold­(I) π-complexes utilizing phosphines and other ligands were characterized previously as well. …”
Section: Introductionmentioning
confidence: 71%
“…5) showed a prominent peak at 445.08, which corresponded to [Cu(BQPN)(CN)] 1+ (calcd m / z 445.13). 42…”
Section: Resultsmentioning
confidence: 99%
“…1e and f), 11 ligand design molecular recognition (Fig. 1g and h), 12,13 photo-assisted oligomer cyanation, 14 and hydrothermal metal-mediated compoundation 15 were also attempted for the activation of nitriles. However, all the above reactions were restricted to the stoichiometric splitting of nitriles, with the generated cyanide anion binding to the catalysts.…”
mentioning
confidence: 99%